Library Management Strategy in Fostering Student Literacy Culture at An-Nizam Private Middle School - Masita, Maya; Rifa'i, Muhammad (Tibanndaru : Jurnal Ilmu Perpustakaan dan Informasi, 2024)
The low literacy of society, especially students in Indonesia, is a concern for the government. Literacy in schools involves the duties and responsibilities of teachers, government, families and society. Cultivating literacy involves students, education, educational staff and parents in practicing literacy as a habit at school. Strategies for realizing a culture of student literacy include strengthening the capacity of facilitators, creating a quality reading culture, expanding access to learning resources, involving the community, and strengthening governance. Student literacy culture can be realized with several strategies that must be implemented, the literacy program carried out by An-Nizam private middle school creates reading corners in every corner of the class, makes routine activities for various subjects scheduled and held in all classes for regular study visits to the school library, as well as celebrating language month is like holding a competition involving literacy activities. also created a project to strengthen the profile of pancasila students which aims to improve students' literacy competencies. the growth of students' literacy culture in the physical and affective environments needs to be accompanied by the implementation of learning strategies that strengthen students' literacy skills. Literacy skills are of course strengthened according to the stages of student literacy development.